1991
DOI: 10.1111/j.1348-0421.1991.tb01540.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serological and Chemical Characteristics of Capsular Polysaccharides of Cryptococcus neoformans var. neoformans Serotype A and Cryptococcus albidus var. albidus

Abstract: The antigenic formula and chemical structure of capsular polysaccharide (CPS) of Cryptococcus albidus var. albidus (C. albidus) were studied in relation to those of C. neoformans var. neoformans serotype A (C. neoformans A). The results of slide agglutination tests with factor sera and reciprocal adsorption experiments showed that antigenic formula of C. albidus was the same as that of C. neoformans A. The soluble CPSs from the two species were obtained from culture supernatants by precipitation with ethanol f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…14;15 The polysaccharide fraction investigated here was eluted from DEAE-Toyopearl column with 0.15 M NaCl under the same conditions as described for the major fraction of C. neoformans. 7 Although the oligosaccharides containing glucuronic acids were very similar to those derived from C. neoformans polysaccharides, striking differences were observed. The results of methylation analysis suggested that the mannose residue substituted at C-2 with glucuronic acid has also the mannosylxylose substituent at C-6 position.…”
Section: Discussionmentioning
confidence: 96%
“…14;15 The polysaccharide fraction investigated here was eluted from DEAE-Toyopearl column with 0.15 M NaCl under the same conditions as described for the major fraction of C. neoformans. 7 Although the oligosaccharides containing glucuronic acids were very similar to those derived from C. neoformans polysaccharides, striking differences were observed. The results of methylation analysis suggested that the mannose residue substituted at C-2 with glucuronic acid has also the mannosylxylose substituent at C-6 position.…”
Section: Discussionmentioning
confidence: 96%
“…The GXM of polysaccharides isolated from Filobasidium species (C. albidus var. albidus) is reported to have a structural resemblance to that of F. neoformans (Ikeda et al, 1991). The major capsular polysaccharide from Tremella mesenterica is also GXM with some variation : the xylose side chain is composed of multimers instead of monomer (Slodki, 1966).…”
Section: Filobasidiella Neoformansmentioning
confidence: 99%
“…The species forming large capsules mostly belonged to the Tremellales and Filobasidiales (Fell et al, 2000). Since the major polysaccharide produced by species of Filobasidiella, Filobasidium, Tremella and Cryptococcus is known to be GXM (Abercombie et al, 1960 ;Cherniak et al, 1988 ;Ikeda et al, 1991 ;Slodki, 1966), we assumed that the genes involved in polysaccharide formation were conserved among these yeasts. Fig.…”
Section: Isolation Of Cnlac1 Homologous Sequencesmentioning
confidence: 99%
“…1996 ). Moreover, the presence of capsular polysaccharides superimposed to the cell wall in Cryptococcus species could also account for the negative results of lysis in these yeasts ( Ikeda et al . 1991 ).…”
Section: Discussionmentioning
confidence: 99%